2014
DOI: 10.1021/ja5046692
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Rosette-Inducing Factor RIF-1 and Analogs

Abstract: Studies on the origin of animal multicellularity have increasingly focused on one of the closest living relatives of animals, the choanoflagellate Salpingoeca rosetta. Single cells of S. rosetta can develop into multicellular rosette-shaped colonies through a process of incomplete cytokinesis. Unexpectedly, the initiation of rosette development requires bacterially produced small molecules. Previously, our laboratories reported the planar structure and femtomolar rosette-inducing activity of one rosette-induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 48 publications
(42 reference statements)
1
47
0
2
Order By: Relevance
“…Additional activity-guided fractionation by HPLC allowed us to isolate pure samples of RIF-1 (35,43) and of the 605-Da sulfonolipid. Purified RIF-1 induced maximal (∼1.5%) rosette development at femtomolar to nanomolar concentrations ( Fig.…”
Section: A Newly Identified Sulfonolipid Activates the Rosette Develomentioning
confidence: 99%
“…Additional activity-guided fractionation by HPLC allowed us to isolate pure samples of RIF-1 (35,43) and of the 605-Da sulfonolipid. Purified RIF-1 induced maximal (∼1.5%) rosette development at femtomolar to nanomolar concentrations ( Fig.…”
Section: A Newly Identified Sulfonolipid Activates the Rosette Develomentioning
confidence: 99%
“…Analysis of the lipid extract of A. machipongonensis revealed that a specific molecule, a sulfonolipid called RIF-1 (rosette inducing factor), is responsible for the induction of colony formation (Figure 2f) [38 ]. RIF-1 synthesized in vitro also induces colony formation [39], and additional molecules, synergizing with RIF-1 in its colony inducing effect have been identified [40]. The sequencing of the genome and transcriptome of S. rosetta has further contributed to our understanding of the putative genome composition of animal ancestors [10].…”
Section: Codosiga Bot Rytismentioning
confidence: 99%
“…81 Key to success was the conversion of a propargylic alkyne group to a 1,3-diol, which was accomplished by trans-hydrosilylation of the propargylic alcohol 92 to give alkenyl silane 93 with high regiocontrol (β:α = 95:5). A subsequent TamaoFleming oxidation 33,34 and stereoselective reduction of the resulting ketone afforded the desired 1,3-syn diol.…”
mentioning
confidence: 99%